(untitled) - Sande, Ken (U.S.A., 2000)
Attorney Ken Sande, executive director of Peacemaker Ministries, lays out biblical principles for managing conflict and reconciling differences between individuals, following Christ's admonition that we live in peace and harmony.
Keywords: Conflict management -- Religious aspects -- Christianity